Penanggulangan Kemiskinan dalam Era Otonomi Daerah - - Mubyarto (Universitas Islam Indonesia, 2001)
This article states the urgency of Poverty Alleviation or Poverty Eradication Law (UU-PPK). The law should contain Indonesian past experiences in poverty eradication programs. The programs are expected to combine the past sectoral, regional, and special programs. The poverty eradication program is intended to reinforce the poor's socio-economic institution so there is a need for brotherhood spirit, community self-help, self-reliance, participation, and decentralization. Active participation is obliged for defining, forming, and assisting the poor. UU-PPK has to state the national commitment to poverty eradication, which will have to be implemented in concrete actions. The programs have to be implemented by the people in every region to develop a prosperous community based on Indonesian socio-culture-religion values, that is Pancasila. In the last part of the article, there is a report on Karangawen, a poor village in Gunungkidul, which is a prototype of a successful IDT program. The conclusion is that poverty eradication program in regional autonomy not only depend on central government's initiatives but more on the regional government and the people themselves.